‘Let’s Collaborate’: Malaysian TVET-Engineering Institution and Industry Partnership - Subri, Ummu Sakinah; Sohimi, Nurul Eizzaty; Mohd Affandi, Haryanti; Mat Noor, Mohd Sallehuddin; Yunus, Faizal Amin Nur (Journal of Technical Education and Training, 2022)
Strategic partnerships are the most important element in the automotive industry. The interaction between two or more parties is important in pursuing the successful planning and implementation of an education and training system in producing a competent workforce. Malaysia is one country that has adopted Public Private Partnership (PPP) as a procurement technique for delivering public sector projects. PPP, taken in its broadest meaning, refers to any arrangement between the public and private sectors for the delivery of public services. However, previous studies indicated that the collaboration between training institutions and industry is still at a weak level. The major constraints were including the failure to understand the work culture of the organization, inconsistency of mission and vision of the organization, and weaknesses of the governance system. Therefore, this study aims to propose a model of TVET-Engineering Governance Structure in Collaboration of Malaysian TVET- Engineering Institution and industry partnership. In this case, data were collected from 115 technologists in three different fields involved mechanical, electric and electronic and civil in Malaysia. Then, the data were analysed using the PLS-SEM 3.3.9 software via the algorithm, bootstrapping and blindfolding method. Through the PLS-SEM approach, this study focuses on the analysis of (a) convergent validity and (b) discriminant validity in which these two validities have six analyses; (i) external loading, (ii) composite reliability, (iii) average variance extracted (AVE), (iv) Fornell-Larcker, (v) cross-loading, and (vi) Heterotrait-Monotrait Ratio (HTMT). Meanwhile, the structural model testing involves the analysis of (i) Multicollinearity (Inner VIF), (ii) Path Coefficient, (iii) R square (R2), (iv) size effect (f2), and (v) Predictive Relevance (Q2). At the end of the analysis, the model that has been developed is relevant to use because each phase meets the conditions that have been set in the PLS-SEM analysis. The result, the governance structure for TVET-Engineering for TVET-Engineering is important since it can contribute to intensifying the Malaysian TVET- Engineering Institution and industry partnership. TVET Institutions must play an important role in fulfilling the demands from the industry and developing innovative skills for students. Future research is suggested to test the model on a wider range of TVET respondents to see its appropriateness.